Survei Kepuasan Pelanggan Berbasis Dekstop (Penelitian Terhadap PT.Gowa Modern Motor) - Mega Khaerunisah; Sutan Moh Arif; Nur Ali (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
PT. Gowa Modern Motor or what we usually know is Hyundai was founded in 2020. Hyundai Motor Company, is an automotive company that is a division of Hyundai Motor Group and is the largest car manufacturer in South Korea. PT. Gowa Modern Motor or Hyundai has a vision and mission, namely "To be the Sole Agent and Respected Distributor" and "Able to compete to provide quality cars, as well as have a uniformity of global standard networks and understand customer desires". Customer satisfaction surveys are certainly needed to find out the customer's response to the quality of service at Hyundai. The purpose of this study is to be able to find out the level of customer satisfaction, using the Research and Development method. The development model used is a linear sequential model consisting of a process of analysis, design, implementation, and testing. . The analysis stage is carried out to find out the needs of the literature that supports the development. The implementation stage is carried out using UML as a modeling medium. The testing stages were carried out four musts, namely functionality, usability, efficiency and portability. Based on the results of the study, it can be concluded that the Customer Satisfaction Survey Information System at PT. Gowa Modern Motor is desktop-based which has met the feasibility of the software in four aspects, namely the functionality aspect by 100%, the usability aspect by 88.2%, the efficiency aspect and the portability aspect.